Evaluasi Konteks Program Pembinaan Prestasi Cabang Olahraga Hockey Di Jawa Timur - Heryanto Nur Muhammad (Journal of Sport Science and Education, 2018)
This study aims to analyze the context of long-term athlete development program in East Java hockey. The method used is the CIPP evaluation model. The research subjects are members of Hockey Indonesia in East Java Province. Data were collected using questionnaires and interviews. Data analysis techniques used descriptive qualitative. Evaluation results in policy-related contexts indicate that the subject of research receives national and local support. Also funding support is different from each other. Working closely with the university in terms of sport science and corporate to get sponsors is expected to improve the performance of research subjects in implementing high performance programs.